The Cynic’s Guide to Compliance: A Constructivist Theory of the Contestation Threshold in Human Rights - Etkin, Başak (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2021)
Wherever the reader may sit on the spectrum of international relations theories, it should hold that whether a state complies with international human rights norms or not translates some other reality beyond the simple act of (non-)conformity. Focusing on such social meanings, constructivism allows to demonstrate how compliance is constitutive of normativity. We combine this constructivist approach with a jaded outlook in order to find out the role contestation, compliance’s cynical ugly twin, plays in normativity. This paper exploits empirical observations concerning contestation in order to address its normative implications, arguing that, up to a certain point contestation nourishes normativity as the norm is taken seriously enough to contest, but that beyond the contestation threshold it becomes damaging. Taking the norms at three stages of implementation, we evaluate their contestation, and therefore, normativity levels. Firstly, we compare UN resolutions on LGBTI+ rights and the right to development as social norms by inspecting voting records. Secondly, we study non-ratifications and reservations made to UN human rights treaties as normativity indicators for emergent legal norms, acknowledging the latter’s unique challenges. Lastly, we take a look at violations of these same treaties as contestation of an established legal norm while questioning the viability of treaty body decisions as a normativity indicator. We conclude that, providing the right indicator is chosen, the contestation threshold is a particularly useful tool when it comes to comparing two or more norms at the same stage of implementation, and only for comparison purposes until the threshold is better quantified.